Разложите на множители:
а) 12x^3-3x^2y-18xy^2
б) 42a^5-6a^4+30a^3
в) 8ab-14a-12b-21

г) x^2-5x-9xy+45y
д) x^4-25y^2
е) 4b^2-0.01c^6
ж) 8a^3+c^3
з) x^9-27
и) 9ab^2-16ac^2
к) -20xy^3+45x^3y

  • а) 12x^3-3x^2y-18xy^2= 3x(4x^2-xy-6y^2)
    б) 42a^5-6a^4+30a^3=6a^3(7a^2-a+5)
    в) 8ab-14a-12b+21= (8ab-14a)+(-12b+21)=2a(4b-7)-3(4b-7)=(4b-7)(2a-3) 

    г) x^2-5x-9xy+45y=(x^2-5x)+(-9xy+45y)=x(x-5)-9y(x-5)=(x-5)(x-9y)
    д) x^4-25y^2=(x^2-5y)(x^2+5y)
    е) 4b^2-0.01c^6=(2b-0,1c^3)(2b+0,1c^3)
    ж) 8a^3+c^3=(2+c)(4-2c+c^2)
    з) x^9-27=(x^3-3)(x^6+3x^3+9)
    и) 9ab^2-16ac^2=a(9b^2-16c^2)=a(3b-4c)(3b+4c)
    к) -20xy^3+45x^3y=-5xy(4y^2-9x^2)=-5xy(2y-3x)(2y+3x)